High-dielectric adjustable polyvinylidene fluoride composite material as well as preparation method and application thereof

By co-doping BST/polyvinylidene fluoride composite materials, the problem of insufficient dielectric properties in microwave communication components has been solved, achieving high dielectric tunability and low dielectric loss, making it suitable for microwave communication equipment and flexible electronic devices.

CN119264582APending Publication Date: 2025-01-07SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411283809.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve high dielectric constant, low dielectric loss, and high dielectric tunability in microwave communication components, and traditional materials present challenges in processing and environmental friendliness.

Method used

A high dielectric tunable polyvinylidene fluoride composite material was prepared by using co-doped BST/polyvinylidene fluoride composite material. The electronic structure was adjusted by La doping, and Cr replaced the B-site element Ti. Combined with the doctor blade coating method, the dielectric properties of the polyvinylidene fluoride composite material were improved.

Benefits of technology

The composite material exhibits high dielectric tunability, low dielectric loss, and high breakdown strength, making it suitable for microwave communication equipment. It also reduces costs and improves processing performance, making it suitable for flexible electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264582A_ABST
    Figure CN119264582A_ABST
Patent Text Reader

Abstract

The invention provides a high-dielectric adjustable polyvinylidene fluoride composite material as well as a preparation method and application thereof. La and Cr co-doped barium strontium titanate filler particles BSTLC are added into the composite material, the doping molar weight of La is 0.3-0.5%, the doping molar weight of Cr is 0.5-0.8%, the surface of the composite material is treated by coupling agents such as 3-aminopropyltrimethoxysilane, 3-vinyloxypropyltrimethoxysilane, gamma-aminopropyltriethoxysilane and the like, and the compatibility between organic-inorganic phase interfaces is realized. The particle size of the BSTLC filler particles is 0.5-1.8 [mu] m, the addition amount is 10-40 wt%, the dielectric constant of the composite material is 12-18, the dielectric loss is 0.02-0.03, the dielectric adjustable rate is 8-12%, and the breakdown strength range is 100-130 kV / mm. The preparation method of the composite material is a scraper coating method. The material can be used as a key basic material for manufacturing equipment such as a phase shifter, a filter and a phase array control antenna in communication equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a high-dielectric adjustable polyvinylidene fluoride composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of communication technology, many fields including high-performance computing, 5G technology, artificial intelligence and electric vehicles require microwave electronic components with excellent performance and high integration to achieve greater miniaturization and functional diversification. In the production of key components of communication technology such as phase shifters, filters and phased array antennas, ceramic / polymer functional composite materials show great potential with their combined two-phase advantages. Microwave modulation devices composed of ceramic / polymer composite materials have the advantages of fast tuning response, small size, good processing performance, low DC drive voltage and environmental friendliness, and are especially suitable for highly integrated circuits.

[0003] Therefore, the development of microwave tunable devices based on ceramic / polymer composites is an inevitable trend to achieve high frequency, miniaturization and cost-effectiveness. Summary of the invention

[0004] The present invention aims to provide a method for preparing a co-doped BST / polyvinylidene fluoride composite material with high dielectric adjustable properties, by introducing donor impurities La to replace A-site elements (Ba, Sr) to adjust the electronic structure and improve the polarization strength under an external electric field, thereby enhancing the overall dielectric adjustability, and introducing acceptor impurities Cr to replace B-site elements (Ti) to neutralize oxygen vacancies generated by high-temperature sintering, thereby reducing dielectric loss.

[0005] In the first aspect, the present invention provides a high dielectric adjustable polyvinylidene fluoride composite material, the composite material is composed of BSTLC and a fluorine-containing ferroelectric polymer; wherein the BSTLC is La and Cr co-doped Ba 0.675 Sr 0.325 TiO 3 .

[0006] Furthermore, in the BSTLC, the molar amount of La doping is 0.3-0.5%, the molar amount of Cr doping is 0.5-0.8%, and the particle size of the BSTLC is 0.5-1.8 μm.

[0007] Furthermore, the amount of BSTLC added to the composite material is 10-40 wt%.

[0008] Furthermore, the fluorine-containing ferroelectric polymer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene; the molecular weight of the fluorine-containing ferroelectric polymer is 100,000 to 500,000.

[0009] Furthermore, when the thickness of the composite material is 4-5 μm, the relative dielectric constant ranges from 12 to 18, the dielectric loss is 0.02 to 0.03, the breakdown strength is 100 to 130 kV / mm, and the dielectric adjustable rate is 8 to 12%.

[0010] In a second aspect, the present invention provides a method for preparing a high dielectric adjustable polyvinylidene fluoride composite material as described above, characterized in that the preparation method of the composite material is a doctor blade coating method, which specifically includes the following steps: S1, preparing BSTLC, and performing surface modification treatment on the BSTLC to obtain surface modified BSTLC; S2, adding organic solvents to the surface modified BSTLC and the fluorine-containing ferroelectric polymer respectively, and after the BSTLC is fully ultrasonicated and the fluorine-containing ferroelectric polymer is fully dissolved, the BSTLC and the fluorine-containing ferroelectric polymer are mixed, and magnetic stirring is performed to obtain a well-dispersed homogeneous composite mixture; S3, applying the composite mixture to a substrate with a coating blade, and then heat-insulating to evaporate the organic solvent to obtain a two-phase composite material film; S4, removing the film from the substrate, and performing gold plating on the surface of the film to obtain a high dielectric adjustable polyvinylidene fluoride composite material.

[0011] Furthermore, the S1 specifically comprises the following steps: S11, weighing analytically pure BaCO according to the stoichiometric ratio; 3 、SrCO 3 、TiO 2 ,La 2 O 3 Cr 2 O 3 , wet ball milling to obtain a mixture; S12, drying, grinding, sieving and calcining the mixture to obtain BSTLC; S13, cooling to room temperature with the furnace after the insulation is completed, sintering the BSTLC and ball milling again to fully crush the powder, discharging, drying and sieving to obtain BSTLC ceramic particles; S14, ultrasonically dispersing the BSTLC ceramic particles in deionized water added with hydrogen peroxide to obtain a BSTLC suspension solution, and then adding a coupling agent to the BSTLC suspension solution, magnetically stirring, centrifuging, washing, drying and sieving to obtain a surface-modified BSTLC.

[0012] Further, in step S11, the ball milling medium is anhydrous ethanol or isopropanol, the mass ratio of zirconia balls for ball milling to the mixed material is (2-5):1, the ball milling speed is 250-350r / min, and the time is 10-14h; in steps S12 and S13, the sintering temperature is 900-1200°C, the holding time is 3-5 hours, the heating rate is 3-5°C / min, and the mesh number of the sieve used in the screening treatment is 80-100 mesh; in step S13, the sintered BSTLC is ball milled again for 10-14h to finally obtain BSTLC ceramic particles with a particle size of 0.5-1.8μm; in step S14, the coupling agent is one of silane coupling agents such as 3-aminopropyltrimethoxysilane, 3-vinyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, etc., and the added amount is 1-8wt% of the mass of the BSTLC ceramic particles.

[0013] Furthermore, in step S2, the organic solvent is N,N-dimethylformamide solvent, the addition ratio of the organic solvent is 1.5 to 3 times that of BSTLC and fluorine-containing ferroelectric polymer, and the duration of magnetic stirring is 0 to 12 hours; in step S3, the coating scraper uses a 30 to 80 μm specification; the substrate is a glass substrate, and the glass substrate is rinsed with deionized water and kept in an oven at 80 to 100°C for 2 to 4 hours before coating; the insulation treatment is insulation in the oven for 4 to 6 hours, and the insulation temperature is 60 to 80°C; the thickness of the two-phase composite thin film material is 4 to 8 μm; in step S4, the gold plating treatment is a magnetron sputtering gold plating treatment using a current of 20 to 40 mA and a duration of 100 to 150 seconds.

[0014] In a third aspect, the present invention provides the application of the high dielectric constant adjustable polyvinylidene fluoride composite material as described above in the field of microwave communication equipment such as phase shifters, filters, phased array antennas, etc.

[0015] The microwave dielectric adjustable, low dielectric constant, and low dielectric loss co-doped BST / polyvinylidene fluoride composite material prepared by the present invention is analyzed and tested by testing equipment such as an X-ray diffractometer (XRD), a particle size analyzer, a scanning electron microscope (SEM), an impedance analyzer, and an LCR meter, and it is determined that the composite material has the following characteristics:

[0016] (1) The phase structure is a uniform composite structure of a BSTLC ceramic phase with a cubic perovskite structure and a PVDF polymer phase.

[0017] (2) The thickness of the composite material is 4 to 5 μm, the surface is flat, smooth and crack-free, and can be tightly bonded to substrates of different properties.

[0018] (3) The relative dielectric constant of the composite film ranges from 12 to 18, the dielectric loss is small (0.02 to 0.03), the breakdown strength is high (100 to 130 kV / mm), and the dielectric adjustability is high (8 to 12%).

[0019] (4) The process is simple and can be applied to substrates of different properties and can be used in flexible electronic devices.

[0020] In summary, the high dielectric adjustable polyvinylidene fluoride composite material provided by the present invention and its preparation method and application have at least the following beneficial effects compared with the prior art:

[0021] 1. In the process of developing microwave communication components, the present invention uses cost-effective polyvinylidene fluoride as the base material, which is easily available in the raw material market in China and is inexpensive. In addition, the amount of silane coupling agent γ-aminopropyltriethoxysilane used is extremely small, further reducing the overall cost. Thanks to the excellent dielectric properties of the base material, the present invention promotes the cost-effective transformation of microwave communication equipment including phase shifters, filters, phased array antennas, etc.;

[0022] 2. The dielectric functional composite material formula proposed in the present invention completely eliminates harmful substances such as lead and cadmium, so the composite material of the present invention is an environmentally friendly choice;

[0023] 3. The composite material prepared by the present invention has excellent dielectric properties, including serialization of dielectric constants, high dielectric adjustability, low dielectric loss and high dielectric strength;

[0024] 4. In terms of processing performance, the dielectric functional composite material of the present invention performs well and is easy to manufacture components with complex structures. It is particularly suitable for flexible wearable devices, which broadens the potential application of microwave dielectric tunable materials and helps to reduce the cost of practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplified descriptions do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.

[0026] Figure 1 This is a surface microscopic morphology of the ceramic phase of the co-doped BST / polyvinylidene fluoride composite material of Example 1 of the present invention;

[0027] Figure 2 This is a surface microscopic morphology of the co-doped BST / polyvinylidene fluoride composite material of Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The high dielectric tunability of BST-based ceramics has been widely studied, but the high dielectric constant and the difficulty in manufacturing complex devices limit its application development. In order to reduce the dielectric constant and improve the processability, functional composite materials are obtained by combining polymers with BST-based ceramic fillers. Compared with BST-based ferroelectric ceramics, among dielectric polymers, ferroelectric polyvinylidene fluoride (PVDF) has attracted widespread attention due to its high dielectric breakdown strength, low dielectric loss, simple processing and low cost. Therefore, people compound BST with PVDF polymers to prepare BST / PVDF composites with excellent dielectric tunability and processing properties.

[0029] In order to further improve the dielectric adjustability and reduce the dielectric loss to maximize the performance benefits of the device, the present invention provides a highly dielectrically adjustable polyvinylidene fluoride composite material and a preparation method and application thereof.

[0030] The present invention is described in detail below in conjunction with specific implementation modes.

[0031] Example 1

[0032] The embodiment of the present invention provides a method for preparing a high dielectric constant adjustable doped BST / polyvinylidene fluoride composite material, comprising the following steps:

[0033] S1. Weigh analytically pure BaCO 3 13.25g, SrCO 3 4.77g, TiO 2 7.93g, La 2 O 3 0.05g, Cr 2 O 3 0.06g.

[0034] S2. Place the prepared mixture in a zirconia ball mill, add anhydrous ethanol of the same mass as the powder, and ball mill at 300 r / min for 12 hours to obtain a mixed slurry, which is then discharged, dried, and sieved.

[0035] S3. Place the crucible containing the mixed material in a muffle furnace at 1150°C for 3 hours for sintering reaction, with a heating rate of 5°C / min.

[0036] S4. After the heat preservation is completed, the furnace is cooled to room temperature, and the powder is ball-milled again to fully crush the powder, and then the material is discharged, dried, and sieved.

[0037] S5, ultrasonically dispersing the obtained target ceramic filler in 100 ml of deionized water containing 30 vol% hydrogen peroxide to obtain a suspension solution of BSTLC, and then weighing analytically pure γ-aminopropyltriethoxysilane according to 2 wt% of the mass of the ceramic particles and adding it to the above suspension, the suspension was magnetically stirred for 5 h, centrifuged and washed with alcohol, dried and sieved to obtain surface-modified BSTLC;

[0038] S6. Weigh two raw materials in a mass ratio of 40wt% BSTLC + 60wt% polyvinylidene fluoride, dissolve and disperse them in N,N-dimethylformamide in a ratio of 2:3 respectively, mix the two different phase systems, and stir them magnetically for 12 hours to obtain a well-dispersed homogeneous composite mixture.

[0039] S7. Use a doctor blade coating method to apply the ceramic / polymer slurry on the surface of a clean glass substrate, and then transfer it to an oven to evaporate the organic solvent. The oven temperature is 80° C. and the temperature is maintained for 5 hours.

[0040] S8. Peel off the film from the glass substrate and plate gold on both sides to obtain a dielectric functional composite material.

[0041] Measured dielectric properties of functional composite materials: dielectric constant ε at 1kHz r =18.5, dielectric loss tanδ = 0.021, dielectric adjustability T at 50kV / mm DC voltage r =12.6%, breakdown strength E b =107.16kV / mm.

[0042] Among them, Figure 1 It can be seen that the particle size and crystal morphology of the co-doped BST / polyvinylidene fluoride composite material of Example 1; Figure 2 It can be seen that the distribution of the filler in the polymer matrix of the co-doped BST / polyvinylidene fluoride composite material of Example 1 shows that the BSTLC particles are uniformly dispersed in the smooth polyvinylidene fluoride matrix, indicating that the blade coating method can effectively prepare a homogeneous composite material.

[0043] Example 2

[0044] The embodiment of the present invention provides a method for preparing a high dielectric constant adjustable doped BST / polyvinylidene fluoride-trifluoroethylene composite material, comprising the following steps:

[0045] S1. Weigh analytically pure BaCO 3 8.83g, SrCO 3 3.18g, TiO 2 5.29g, La 2 O 3 0.03g, Cr 2 O3 0.04g.

[0046] S2. Place the prepared mixture in a zirconia ball mill, add anhydrous ethanol of the same mass as the powder, and ball mill at 250 r / min for 14 hours to obtain a mixed slurry, which is then discharged, dried, and sieved.

[0047] S3. Place the crucible containing the mixed material in a muffle furnace at 1200°C for 2.5 hours for sintering reaction, with a heating rate of 3°C / min.

[0048] S4. After the heat preservation is completed, the furnace is cooled to room temperature, and the powder is ball-milled again to fully crush the powder, and then the material is discharged, dried, and sieved.

[0049] S5, ultrasonically dispersing the obtained target ceramic filler in 120 ml of deionized water containing 30 vol% hydrogen peroxide to obtain a suspension solution of BSTLC, and then weighing 4 wt% of the mass of the ceramic particles of analytically pure 3-aminopropyltrimethoxysilane and adding it to the above suspension, the suspension was magnetically stirred for 3 h, centrifuged and washed with alcohol, dried, sieved, and obtained surface-modified BSTLC;

[0050] S6. Weigh two raw materials in a mass ratio of 20wt% BSTLC + 80wt% polyvinylidene fluoride-trifluoroethylene, dissolve and disperse them in N,N-dimethylformamide in a ratio of 3:5, mix the two different phase systems, and stir them magnetically for 13 hours to obtain a well-dispersed homogeneous composite mixture.

[0051] S7. Use a doctor blade coating method to apply the ceramic / polymer slurry on the surface of a clean glass substrate, and then transfer it to an oven to evaporate the organic solvent. The oven temperature is 80° C. and the temperature is maintained for 4 hours.

[0052] S8. Peel off the film from the glass substrate and plate gold on both sides to obtain a dielectric functional composite material.

[0053] Measured dielectric properties of functional composite materials: dielectric constant ε at 1kHz r =14.3, dielectric loss tanδ=0.029, dielectric adjustability T at 50kV / mm DC voltage r =6.4%, breakdown strength E b =123.82kV / mm.

[0054] Example 3

[0055] The embodiment of the present invention provides a method for preparing a high dielectric constant adjustable doped BST / polyvinylidene fluoride-chlorotrifluoroethylene composite material, comprising the following steps:

[0056] S1. Weigh analytically pure BaCO 3 7.36g, SrCO3 2.65g, TiO 2 4.41g, La 2 O 3 0.05g, Cr 2 O 3 0.02g.

[0057] S2. Place the prepared mixture in a zirconia ball mill, add anhydrous ethanol of the same mass as the powder, and ball mill at 300 r / min for 13 hours to obtain a mixed slurry, which is then discharged, dried, and sieved.

[0058] S3. Place the crucible containing the mixed material in a muffle furnace at 900°C for 5 hours for sintering reaction, with a heating rate of 5°C / min.

[0059] S4. After the heat preservation is completed, the furnace is cooled to room temperature, and the powder is ball-milled again to fully crush the powder, and then the material is discharged, dried, and sieved.

[0060] S5, ultrasonically dispersing the obtained target ceramic filler in 100 ml of deionized water containing 30 vol% hydrogen peroxide to obtain a suspension solution of BSTLC, and then weighing 4 wt% of the mass of the ceramic particles of analytically pure 3-aminopropyltrimethoxysilane and adding it to the above suspension, the suspension was magnetically stirred for 3 h, centrifuged and washed with alcohol, dried and sieved to obtain surface-modified BSTLC;

[0061] S6. Weigh two raw materials in a mass ratio of 10wt% BSTLC + 90wt% polyvinylidene fluoride-chlorotrifluoroethylene, dissolve and disperse them in N,N-dimethylformamide in a ratio of 3:5, mix the two different phase systems, and stir them magnetically for 13 hours to obtain a well-dispersed homogeneous composite mixture.

[0062] S7. Use a doctor blade coating method to apply the ceramic / polymer slurry on the surface of a clean glass substrate, and then transfer it to an oven to evaporate the organic solvent. The oven temperature is 80° C. and the temperature is maintained for 4 hours.

[0063] S8. Peel off the film from the glass substrate and plate gold on both sides to obtain a dielectric functional composite material.

[0064] Measured dielectric properties of functional composite materials: dielectric constant ε at 1kHz r =13.2, dielectric loss tanδ=0.026, dielectric adjustability T at 50kV / mm DC voltage r =4.1%, breakdown strength E b =126.74kV / mm.

[0065] Comparative Example 1

[0066] The embodiment of the present invention provides a method for preparing a BST / polyvinylidene fluoride composite material, comprising the following steps:

[0067] S1. Weigh analytically pure BaCO 3 6.66 g, SrCO 3 2.40g, TiO 2 3.99g.

[0068] S2. Place the prepared mixture in a zirconia ball mill, add anhydrous ethanol of the same mass as the powder, and ball mill at 350 r / min for 14 hours to obtain a mixed slurry, which is then discharged, dried, and sieved.

[0069] S3. Place the crucible containing the mixed material in a muffle furnace at 1300°C for 2 hours for sintering reaction, with a heating rate of 3°C / min.

[0070] S4. After the heat preservation is completed, the furnace is cooled to room temperature, and the powder is ball-milled again to fully crush the powder, and then the material is discharged, dried, and sieved.

[0071] S5, ultrasonically dispersing the obtained target ceramic filler in 80 ml of deionized water containing 30 vol% hydrogen peroxide to obtain a suspension solution of BST, and then weighing 4 wt% of the mass of the ceramic particles of analytically pure 3-vinyloxypropyltrimethoxysilane and adding it to the above suspension, the suspension was magnetically stirred for 3 hours, centrifuged and washed with alcohol, dried, and sieved to obtain surface-modified BST;

[0072] S6. Weigh two raw materials in a mass ratio of 40wt% BSTLC + 60wt% polyvinylidene fluoride, dissolve and disperse them in N,N-dimethylformamide in a ratio of 1:3 respectively, mix the two different phase systems, and stir them magnetically for 14 hours to obtain a well-dispersed homogeneous composite mixture.

[0073] S7. Use a doctor blade coating method to apply the ceramic / polymer slurry on the surface of a clean glass substrate, and then transfer it to an oven to evaporate the organic solvent. The oven temperature is 60° C. and the temperature is maintained for 6 hours.

[0074] S8. Peel off the film from the glass substrate and plate gold on both sides to obtain a dielectric functional composite material.

[0075] Measured dielectric properties of functional composite materials: dielectric constant ε at 1kHz r =15.1, dielectric loss tanδ=0.033, dielectric adjustability T at 50kV / mm DC voltage r =4.6%, breakdown strength E b =74.84kV / mm.

[0076] Comparative Example 2

[0077] The embodiment of the present invention provides a method for preparing a BST / polyvinylidene fluoride-trifluoroethylene composite material, comprising the following steps:

[0078] S1. Weigh analytically pure BaCO 3 7.99g, SrCO 3 2.88g, TiO 2 4.79g.

[0079] S2. Place the prepared mixture in a zirconia ball mill, add anhydrous ethanol of the same mass as the powder, and ball mill at 320 r / min for 12 hours to obtain a mixed slurry, which is then discharged, dried, and sieved.

[0080] S3. Place the crucible containing the mixed material in a muffle furnace at 1200°C for 3 hours for sintering reaction, with a heating rate of 4°C / min.

[0081] S4. After the heat preservation is completed, the furnace is cooled to room temperature, and the powder is ball-milled again to fully crush the powder, and then the material is discharged, dried, and sieved.

[0082] S5, ultrasonically dispersing the obtained target ceramic filler in 90 ml of deionized water containing 30 vol% hydrogen peroxide to obtain a suspension solution of BST, and then weighing 2 wt% of the mass of the ceramic particles of analytically pure γ-aminopropyltriethoxysilane to add to the above suspension, the suspension was magnetically stirred for 4 hours, centrifuged and washed with alcohol, dried, sieved, and surface-modified BST was obtained;

[0083] S6. Weigh two raw materials in a mass ratio of 10wt% BST + 90wt% polyvinylidene fluoride-trifluoroethylene, dissolve and disperse them in N,N-dimethylformamide in a ratio of 2:3 respectively, mix the two different phase systems, and stir them magnetically for 14 hours to obtain a well-dispersed homogeneous composite mixture.

[0084] S7. Use a doctor blade coating method to apply the ceramic / polymer slurry on the surface of a clean glass substrate, and then transfer it to an oven to evaporate the organic solvent. The oven temperature is 80° C. and the temperature is maintained for 5 hours.

[0085] S8. Peel off the film from the glass substrate and plate gold on both sides to obtain a dielectric functional composite material.

[0086] Measured dielectric properties of functional composite materials: dielectric constant ε at 1kHz r =11.3, dielectric loss tanδ=0.019, dielectric adjustability T at 50kV / mm DC voltage r =0.6%, breakdown strength E b =106.46kV / mm.

[0087] Table 1 Properties of the composite films prepared in Examples 1 to 3 and Comparative Examples 1 to 2

[0088]

[0089]

[0090] As can be seen from Table 1, the composite films prepared in Examples 1 to 3 of the present application have higher dielectric constants, dielectric adjustability and breakdown strength than the composite films prepared in Comparative Examples 1 to 2 at the same filler content, and have lower dielectric losses. This is mainly attributed to the doped modified BSTLC ceramic filler, where the donor impurity La replaces the A-site elements (Ba, Sr) to adjust the electronic structure, increase the polarization strength under the external electric field, and increase the overall dielectric adjustability of the composite material. The introduction of the acceptor impurity Cr to replace the B-site element (Ti) can, on the one hand, neutralize the oxygen vacancies generated during high-temperature sintering and reduce dielectric losses; on the other hand, Cr enters the lattice and tends to segregate at the grain boundaries, playing a role in pinning the grain boundaries, so that the ceramic grains have a smaller size and a more uniform structure, which has a positive contribution to the improvement of the above-mentioned performance.

[0091] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.

Claims

1. A high dielectric adjustable polyvinylidene fluoride composite material, characterized in that: The composite material consists of BSTLC and fluorine-containing ferroelectric polymer; Wherein, the BSTLC is La and Cr co-doped Ba 0.675 Sr 0.325 TiO3.

2. The high dielectric adjustable polyvinylidene fluoride composite material according to claim 1, characterized in that: In the BSTLC, the molar amount of La doping is 0.3-0.5%, the molar amount of Cr doping is 0.5-0.8%, and the particle size of the BSTLC is 0.5-1.8 μm.

3. The high dielectric adjustable polyvinylidene fluoride composite material according to claim 1, characterized in that: The amount of BSTLC added to the composite material is 10-40 wt %.

4. The high dielectric adjustable polyvinylidene fluoride composite material according to claim 1, characterized in that: The fluorine-containing ferroelectric polymer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene; the molecular weight of the fluorine-containing ferroelectric polymer is 100,000-500,000.

5. The high dielectric adjustable polyvinylidene fluoride composite material according to claim 1, characterized in that: When the thickness of the composite material is 4-5 μm, the relative dielectric constant ranges from 12 to 18, the dielectric loss is 0.02 to 0.03, the breakdown strength is 100 to 130 kV / mm, and the dielectric adjustable rate is 8 to 12%.

6. The method for preparing a high dielectric adjustable polyvinylidene fluoride composite material according to any one of claims 1 to 5, characterized in that: The preparation method of the composite material is a doctor blade coating method, which specifically comprises the following steps: S1, preparing BSTLC, and performing surface modification treatment on the BSTLC to obtain a surface-modified BSTLC; S2, adding organic solvent to the surface-modified BSTLC and the fluorine-containing ferroelectric polymer respectively, after the BSTLC is fully ultrasonicated and the fluorine-containing ferroelectric polymer is fully dissolved, the BSTLC and the fluorine-containing ferroelectric polymer are mixed, and magnetic stirring is performed to obtain a well-dispersed homogeneous composite mixture; S3, coating the composite mixture onto the substrate with a coating blade, and then heat-insulating the substrate to evaporate the organic solvent to obtain a two-phase composite material film; S4. Peeling off the film from the substrate, and performing gold plating on the surface of the film to obtain a high dielectric adjustable polyvinylidene fluoride composite material.

7. The method for preparing the high dielectric adjustable polyvinylidene fluoride composite material according to claim 6, characterized in that: The S1 specifically includes the following steps: S11, weighing analytically pure BaCO3, SrCO3, TiO2, La2O3, and Cr2O3 according to the stoichiometric ratio, and performing wet ball milling to obtain a mixture; S12, drying, grinding, sieving and calcining the mixture to obtain BSTLC; S13, after the heat preservation is completed, the furnace is cooled to room temperature, the BSTLC is sintered and ball-milled again to fully crush the powder, and the material is discharged, dried, and sieved to obtain BSTLC ceramic particles; S14, ultrasonically dispersing the BSTLC ceramic particles in deionized water with hydrogen peroxide to obtain a BSTLC suspension solution, then adding a coupling agent to the BSTLC suspension solution, and subjecting the solution to magnetic stirring, centrifugation, washing, drying, and sieving to obtain a surface-modified BSTLC.

8. The method for preparing the high dielectric adjustable polyvinylidene fluoride composite material according to claim 7, characterized in that: In step S11, the ball milling medium is anhydrous ethanol or isopropanol, the mass ratio of the zirconia balls used for ball milling to the mixed material is (2-5):1, the ball milling speed is 250-350 r / min, and the time is 10-14 h; In steps S12 and S13, the sintering temperature is 900-1200° C., the holding time is 3-5 hours, the heating rate is 3-5° C. / min, and the mesh number of the sieve used in the sieving treatment is 80-100 mesh; In step S13, the sintered BSTLC is ball-milled again for 10 to 14 hours to finally obtain BSTLC ceramic particles with a particle size of 0.5 to 1.8 μm; In step S14, the coupling agent is one of silane coupling agents such as 3-aminopropyltrimethoxysilane, 3-vinyloxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane, and the added amount is 1-8 wt % of the mass of the BSTLC ceramic particles.

9. The method for preparing the high dielectric adjustable polyvinylidene fluoride composite material according to claim 6, characterized in that: In step S2, the organic solvent is N,N-dimethylformamide solvent, the addition ratio of the organic solvent is 1.5 to 3 times of BSTLC and fluorine-containing ferroelectric polymer, and the duration of magnetic stirring is 0 to 12 hours; In step S3, the coating scraper uses a specification of 30-80 μm; the substrate is a glass substrate, which is rinsed with deionized water and kept in an oven at 80-100° C. for 2-4 hours before coating; the heat preservation treatment is kept in the oven for 4-6 hours at a temperature of 60-80° C.; the thickness of the two-phase composite film material is 4-8 μm; In step S4, the gold plating process is a magnetron sputtering gold plating process using a current of 20 to 40 mA and a duration of 100 to 150 seconds.

10. Application of the high dielectric tunable polyvinylidene fluoride composite material according to any one of claims 1 to 5 in the field of microwave communication equipment such as phase shifters, filters, and phased array antennas.

Citation Information

Patent Citations

  • High-dielectric tunability ceramic / high polymer functional composite and preparation method

    CN105778361A

  • Barium strontium titanate porous ceramic / polyvinylidene fluoride composite material and preparation method thereof

    CN113201195A

  • Dielectric ceramic composition and stacked ceramic capacitor

    CN1249286A